Southeast Kansas Winter Wheat Variety Test Results - 2021 - G. Sassenrath; L. Mengarelli; J. Lingenfelser; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2022)
This is a summary of the winter wheat production conditions in southeast Kansas in 2020-2021 and the results of the winter wheat variety testing. Wheat production in 2021 benefited from dry conditions at planting and harvest. Overall yields were above multi-year averages. As in previous years, soft red winter wheat out-yielded hard red winter wheat varieties.
Keywords: winter wheat varieties; crop performance; hard wheat; soft wheat